Eco-Theology as an Ontological Foundation for Islamic Education in The 21st Century - Uswatun Hasanah; Khoirul Umam Addzaky (Vidya Karya, 2026)
The global ecological crisis has become one of the most urgent challenges of the 21st century, yet educational responses within Islamic contexts often remain limited to moral exhortations or cognitive instruction. This situation raises a fundamental question about the ontological basis of Islamic education and how it can address the ecological dimension of human existence. The present study seeks to examine eco-theology as an ontological foundation for Islamic education, exploring how the relationship between God, humanity, and nature can reshape the aims and practices of education. A review of philosophical and theological literature reveals a research gap. While many studies discuss environmental ethics in Islam, few investigate eco-theology as a foundational ontology for education. To address this gap, this study employs a qualitative philosophical method, using textual analysis of classical sources (the Qur’an, Hadith, and Islamic scholarship) alongside contemporary works on Islamic philosophy of education and environmental theology. The findings suggest that eco-theology provides three key ontological principles: tawhid (the unity of existence), khalifah (human stewardship), and Mizan (cosmic balance). These principles define human beings not only as spiritual and rational but also as ecological entities. As a result, Islamic education must integrate ecological consciousness into its philosophy and praxis. The study concludes that eco-theology, understood ontologically, reframes Islamic education for the 21st century. Its implications include curriculum development that embeds environmental ethics, pedagogies that use nature as a learning space, and identity formation that links faith with ecological responsibility.